1983
DOI: 10.1073/pnas.80.18.5734
|View full text |Cite
|
Sign up to set email alerts
|

Cycling of peripheral blood and marrow lymphocytes in cyclic neutropenia.

Abstract: A 16-monthrold male patient with cyclic neutropenia was found to have cyclic fluctuations of monocytes, lymphocytes, platelets, and eosinophils in the peripheral blood. Changes in lymphocyte counts were not obviously related to B, T, or natural killer cells. All classes of immunoglobulins were elevated throughout the cycle. Studies of the marrow morphology revealed remarkable cyclic oscillations of lymphoid as well as myeloid lineage cells. Granulocyte-macrophage progenitors (CFU-c) cycled and were virtually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…This finding is similar to that in other cyclic hematopoietic disorders, including cyclic neutropenia 10 and cyclic thrombocytopenia, 13 and could be consistent with isolated involvement of a single lineage with secretion of cytokines or chemokines leading to secondary cycling of other cell types or with primary involvement of a hematopoietic precursor. In order to explore the etiology of the cycling in EAE, serum and intracellular cytokine and chemokine levels were examined every 2-3 days over the course of an entire cycle in four subjects on no treatment (n=3) or stable, low-dose prednisone therapy (n=1).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This finding is similar to that in other cyclic hematopoietic disorders, including cyclic neutropenia 10 and cyclic thrombocytopenia, 13 and could be consistent with isolated involvement of a single lineage with secretion of cytokines or chemokines leading to secondary cycling of other cell types or with primary involvement of a hematopoietic precursor. In order to explore the etiology of the cycling in EAE, serum and intracellular cytokine and chemokine levels were examined every 2-3 days over the course of an entire cycle in four subjects on no treatment (n=3) or stable, low-dose prednisone therapy (n=1).…”
Section: Discussionsupporting
confidence: 72%
“…12,13 Of note, cycling of multiple additional cell lineages, including eosinophils, platelets, monocytes and lymphocytes, has been reported in patients with these disorders. 10,13 Furthermore, populations of abnormal lymphocytes, specifically large granular lymphocytes, are often present in patients with the adult onset form of cyclic neutropenia 11 and have been described in cyclic thrombocytopenia. 12 Although mutations in neutrophil elastase (ELANE) 14 have been identified in many patients with cyclic neutropenia, the role of these mutations in neutrophil cycling remains controversial.…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic neutropenia (a type of congenital neutropenia, is an autosomal dominant disorder that is characterized by oscillating levels of blood neutrophils, monocytes, platelets, reticulocytes and lymphocytes, usually with a 21-day periodicity 12,134,135,136,137 . Family studies later confirmed the inheritance pattern and the absence of associated hematological and non-hematological malignancies 138 .…”
Section: Cyclic Neutropeniamentioning
confidence: 99%
“…There may also be cycling of monocytes, eosinophils, lymphocytes, platelets, and reticulocytes (Dresch et al 1977; Engelhard et al 1983). Patients with this disease regularly have fever, skin infection, stomatitis, and occasionally, lifethreating infections during the neutropenic periods.…”
mentioning
confidence: 99%